Understanding the linkage between agricultural productivity and nutrient consumption: Evidence from Uganda - Ulimwengu, John M.; Liverpool-Tasie, Lenis Saweda; Randriamamonjy, Josee; Ramadan, Racha (International Food Policy Research Institute, 2011)
The prevalence of malnutrition across a predominantly agrarian country like Uganda and its potential economic implications indicate the importance of understanding the link between agricultural productivity and nutrient consumption. Such an understanding will highlight the importance of different nutrients (and foods) available across Uganda, thus guiding policymakers in prioritizing and developing appropriate programs to tackle malnutrition and improve agricultural productivity. This study contributes to the more recent literature on the linkage between nutrition and productivity by exploring the impact of various micronutrients, in addition to caloric intake, on agricultural productivity in Uganda. Using a structural equations model (SEM), estimation results clearly reveal the bidirectional relationship between productivity and nutrient intake. Labor productivity elasticity with respect to nutrient intake varies between 0.04 for vitamin B12 and 0.01 for Iron. Our findings suggest that labor productivity increases agricultural income as one would expect. We also find that nutrient intake as well as labor productivity positively affect agricultural income in Uganda. Overall, results indicate that agricultural productivity in Uganda is likely to be enhanced if nutrients intake is significantly increased.